Analysis of the Indonesian Government’s Efforts in Overcoming Public Data Leak Cases - Rahma, Sintya Dewi; Putra, Bonifasius Ananda; Djarwadi, Lukman Fahmi (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2023)
Public data leaks pose significant challenges to individuals’ privacy and national security in the digital age. This paper provides a focused analysis of the Indonesian government’s efforts to address public data leak incidents. It begins with an overview of the increasing prevalence of data leaks in Indonesia, emphasizing the need for effective government responses. The analysis delves into the existing legal framework and regulations governing data protection and cybersecurity, highlighting their strengths and limitations. It assesses the government’s initiatives, policies, and technological measures designed to prevent and mitigate data leaks, with case studies illustrating specific incident responses. Challenges and constraints faced by the government, such as enforcement issues and resource limitations, are examined. International best practices are also considered to provide comparative insights.The analysis concludes with recommendations for strengthening the government’s efforts, emphasizing policy improvements, legal reforms, and capacity building. This paper underscores the pivotal role of government action in safeguarding public data, privacy, and human security in the digital era.